THIS ANALYSIS OF THE EFFECT OF TAX REVENUE SHARING TO THE CONVERGENCE OF LOCAL ECONOMIC GROWTH - Boby Wijonarko (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2011)
This scientific article analyzed the correlation of tax revenue sharing and other factors to local regions economic growth convergence in java and bali. It was based on the fact that role of tax became more significant to state revenue because almost 70% of state revenue was yield by tax in 2001. Since Indonesia goverment implement fiscal decentralization, central goverment made tax revenue sharing transfer form. The transfer of tax revenue sharing made the local regions economic growth increase . beside that, there were other factors that had an important role to increase local regions economic growth such as society education quality, society saving, physical capital(house), and the effectiveness and effieciency of development expenditure allocation. If local goverment(regency and city) could control those factors, so the high level local economic growth convergence could be achieved. Based on the cross-section data analysis in 2001 and used OLS model, tax revenue sharing had positive effect to the economic growth of regency and city in java and bali. Unfortunately, this effect could not create economic growth convergence because tax revenue sharing had only significant effect to city growth. Beside that, the poorer local goverment could not control the supporting factor of economic growth escalation so that the effective and efficient tax policy and the amprovement of local governance in order to achieve the local regions economic growth convergence .